Música Cimática: processos composicionais provenientes de experiências físicas para geração de materiais sonoros - Silva, Halley Chaves da (2018)
This paper is divided into two parts: (A) artistic production and (B) article. The artistic production includes compositions that belong to the electroacoustic phase of my academic career, which can be applied in the development of new technologies for musical composition, in addition two unpublished pieces of music, as a result of the current research: Lissajous x Chladni Op. 33 and Santa Iemanjá Op. 34. This work aims to use the Cymatics phenomenon, the influence of sound on physical environment, as a compositional process to develop chamber and electroacoustic pieces. The article presents the compositional memorial of the two abovementioned Cymatics pieces of music. For this aim, we employed bibliographic analysis and experimental methods with a qualitative approach for discussing the data. We first investigated the physical aspects of Cymatics in order to apply them in the composition of sound materials. These aspects are based on the theory developed by the physicist Hans Jenny (1904-1972), which mathematically formalizes the 2D projection of Chladni (1756-1827) figures. As a source for structuring the musical pieces, we applied the experience required for the composition of Symphony no. 1, Op. 28, which was described in the present work, as well as the completion of sound-physical experiments that generated compositional materials. In order to describe such materials, data was split into four categories: sound, material, intentional and technical specifications. The work Lissajous x Chladni, Op. 33 puts forward an audiovisual idea of ​​antagonism between the physical and the virtual. It is a minimalist piece of work built through a Pure Data Extended patch that simulates an oscilloscope with virtual Lissajous figures and cymatics figures on the water through the physical environment. The second piece is Santa Iemanjá, Op. 34. This acousmatic piece was composed to be played on the electroacoustic table, which is an electronic version of the vibroacoustic table, especially built for the attainment of cymatics appreciation of this piece. As a result, in addition to the previously described pieces, we point out in the conclusions challenges and possibilities that cymatics music offers composers.